KERENTANAN BEBERAPA JENIS KAYU TERHADAP SERANGAN KUMBANG AMBROSIA - Paimin Sukartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
Ambrosia beetles belong to the most destructive wood borers that attack fresh cut logs. To determine the damage of some wood species caused by the pests, a field study was conducted by calculating the intensity of the beetle infestation on the surface of logs in a log yard of a logging operation, and on the surface of cores of peeled logs of a plywood mill.Observations on the yard showed that most of the logs had been severely damaged by the beetles. Hundreds of holes per-square meter were found on the surface of the logs. Meranti (Shorea spp) logs might belong to the most susceptible ones, and then consecutively followed by the bangkirai (S.laevifolia), mersawa (Anisoptera spp), keruing (Dipterocarpus spp), and others. Only few logs seemed to be intact.Many holes of the beetle infestation were also appeared on the surface of cores of the meranti species, but not so on the keruing's. That could be implied that the beetles attacking the meranti are able to tunnel very deep, to reach the heart of the wood group.